Culinary Places Recommendation System in Bekasi City Using the Simple Additive Weighting Method - Fata Nidaul Khasanah; Herlawati Herlawati (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2021)
Bekasi city, based on data from the Central Bureau of Statistics (BPS) in 2018, shows the average Economic Growth Rate (LPE) of 5.82% from 2013 to 2016. Based on this growth, Bekasi city has business opportunities, for example culinary business, that has already spread around Bekasi city. The number of culinary places can cause problems when visitors determine culinary places that fit their criteria. Many visitors usually rely on information from relatives in determine culinary places, so this allows a mismatch between the recommendations of relatives and the criteria they want. Based on the problem, one of the proposed solutions needs to be made a method to support decisions that can provide recommendations in determining culinary places for visitors. The method used in determining the recommendation of culinary places is Simple Additive Weighting (SAW). In the process of calculating the method there are alternatives and assessment criteria used, there are several assessment criteria, namely price, number of menus, rating, and distance. The result shows the recommended alternative culinary place is the eighth alternative (A8) since the alternative has the highest preference value of 0.85. Therefore, the proposed system can be integrated in the culinary website to support user in choosing the culinary place.